HYGIENIC CONDITIONS OF THE COCKTAIL PROCESS OF MEDICAL PERSONNEL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The economic reforms being carried out in the Republic of Uzbekistan leads to the emergence of new types and modern medical institutions. Features of the process of exposure to the body when studying the conditions and nature of the workflow of medical personnel working with corpses (contact with allergens of drugs, toxic substances, pathogenic microorganisms, overstrain of the visual analyzer, stereotypical movements of small muscles of the working arm, nervous and emotional tension), Adverse factors were identified that caused inconveniences in the arrangement of the premises of the forensic medical examination and pathologists, various equipment, tool designs, imperfection of fillers and materials of the drug.